Analysis of Community Behavior in Domestic Waste Management in The Sub-District Dom Aleixo, Nai Feto and Cristo Rei, Dili, Timor Leste - Noviyantin; Delia Ximenes A. Belo (Jurnal Perkotaan, 2023)
Dili is the capital of Timor-Leste which faces problems in managing and handling waste that has not been optimally carried out because waste is something discarded from the results of human and natural activities that do not have economic value. We have three locations in Dili for the research, Dom Aleixo, Nai Feto and Cristo Rei sub-districts. The purpose of this study was to determine the relationship between attitudes and knowledge of the community towards the waste management system in the sub-districts of Dom Aleixo, Nai Feto and Cristo Rei. This study used a descriptive quantitative method, namely data collection is done by interviewing in the form of a questionnaire using the Kobo toolbox application and the method used in sampling is random sampling. The sample size taken in this study was 332 respondents. Data analysis used the SPSS 25.0 application, namely, to analyze univariate and bivariate using the chi square test. Results reveal a noteworthy P-value of 1.084 (>0.05) from the chi-square test, indicating a significant relationship between community knowledge and waste management practices. Notably, the demographic profile shows that most respondents possess at least a high school education and fall within the 35-50 age range, suggesting a potential for high reasoning power concerning environmental conservation. However, despite adequate knowledge about waste characteristics, the findings show a disconnect in translating this knowledge into environmentally friendly practices. Furthermore, the study recorded a chi-square value of 2.57 (>0.05) concerning the relationship between community attitudes and waste management actions. This indicates that while there is a relationship, it does not translate into a positive environmental outcome, as many respondents engage in poor waste disposal practices. The study underscores the need for more effective educational and policy interventions to bridge the gap between environmental knowledge and action in Dili's waste management system.